٢٠٠٣- العلاقات السودانیة - الاثیوبیة ١٩٥٤ - أ.م.د. منى حسین عبید (College of Education for Women, 2019)
The Horn of Africa region is one of the most important strategic areas according to the geopolitical classification of the world, thus the region held a great importance throughout two historical ears specially for possessing internal attraction factors either for it's natural resources or for what it represent as a central point for maritime transport. Adding to that the region witnessed ethnic and political contradictions as well as cultural differences. Because of the importance of the Horn of Africa region it has become Fulcrum of the conflict among European powers Which worked hard to impose its influence on this region for the purpose of monopolizing the Geographical and strategic advantages which managed European powers, after the Berlin Conference in (1884-1885) to impose it's influence on some parts of the region Prompting Ethiopia to coordinate with the Western powers Pretext that it is a Christian state to cooperate with them in the division of the territory of the Horn of Africa, Ethiopia, managed to share their dreams in controlling the States (Eritrea, Djibouti, Somalia, Sudan) and draw political boundaries. This division disregarded (The tribes living on both sides of the borders) the right to self-determination, imposing impact on Ethiopia's relations with neighboring countries, including Sudan from the west The division led both countries to fall into conflicts as well as borders and ethnic problems which lasted for several political eras and for several successive regimes, it also gave way to regional powers allowing these powers to practice there role to put pressure on many Arab countries, especially Egypt and Sudan, which has had an impact on both countries safety. The entitled thesis (Sudanese-Ethiopian contemporary relations) will discuss the nature of the relation that linked the two countries especially in light of successive Sudanese regimes which significantly influenced the course of that relation.